Competitiveness Indicators : A Theoretical and Empirical Assessment - Marsh, Ian (IMF Working Papers; Working Paper ;, 1994)
This paper discusses five indicators of competitiveness: real exchange rates based on consumer price indices, export unit values of manufacturing goods, the relative price of traded to nontraded goods, normalized unit labor costs in manufacturing, and the ratio of normalized unit labor costs to value-added deflators in manufacturing. It discusses how each of these measures is associated with changes in a country's balance of trade in goods and nonfactor services and examines the relationship among these indicators. It then examines the empirical performance of three of the indicators in terms of their ability to explain trade flows.